Association between basal proteinuria levels and pregnancy outcomes in familial Mediterranean fever. (16th November 2020) - Iskender, D.; Kara, O.; Ozturk Kaymak, A.; Daglar, H. K.; Kirbas, A.; Iskender, C. T.; Kaymak, O.; Celen, S.
Abstract: We aimed to investigate whether proteinuria in the first trimester of pregnancy in Familial Mediterranean fever (FMF) patients has an impact on pregnancy outcome and perinatal and neonatal outcome of pregnancies. A total of 66 pregnant with FMF were compared with healthy controls at the same gestational weeks. Patients with FMF had a higher antenatal hospitalisation rate (34.8% vs. 6.1%, respectively, p <  .01) and higher rate of 2 or more miscarriages. FMF patients with or without obstetric complications also had a similar amount of 24-h urine proteinuria in the first trimester. Patients on colchicine therapy during pregnancy had more frequent attacks in pregnancy (59.3% vs. 18.2%, respectively, p: . 012). The rates of preeclampsia, preterm delivery, foetal anomalies, small for gestation age neonates and primary caesarean rate were similar between groups. In conclusion; FMF had no significant impact on pregnancy. Neither attacks in pregnancy nor basal proteinuria were associated with adverse outcomes. Impact statement: What is already known on this subject? Familial Mediterranean fever (FMF) is an autosomal recessive disease characterised by inflammation of the serosal, synovial and cutaneous tissues with recurrent attacks. One of the most serious complications of FMF is amyloidosis that can cause end-stage renal disease. Outcomes of FMF on pregnancy have been analysed by only few studies. Amyloidosis based on the initial renal function may adversely affect pregnancies. It has been reported that FMF patients with renal amyloidosis may suffer pregnancy complications to a greater extent. What do the results of this study add? There have been few studies on the correlation between FMF, proteinuria and pregnancy outcomes. In our study we found that FMF had no significant impact on pregnancy. Neither attacks in pregnancy nor basal proteinuria were associated with adverse outcomes. What are the implications of these findings for clinical practice and/or further research? Our study suggested that FMF had no relationship between pregnancy outcomes. However, our study population is relatively small. It will contribute to comprehensive studies involving a larger population. Future studies should be performed to investigate the effects of basal proteinuria in pregnancy with FMF.